Great Christian jurists and legal collections in the first millennium / edited by Philip L. Reynolds. - Reynolds, Philip Lyndon, 1950- (Law and Christianity., 2019)
Great Christian Jurists and Legal Collections in the First Millennium is a systematic collection of essays describing how Christian leaders and scholars of the first millennium in the West contributed to law and jurisprudence and used written norms and corrective practices to maintain social order and to guide people from this life into the next. With chapters on topics such as Roman and post-Roman law, church councils, the papacy, and the relationship between royal and ecclesiastical authority, as well as on individual authors such as Lactantius, Ambrosiaster, Augustine, Leo I, Gelasius I, and Gregory the Great, this book invites a more holistic and realistic appreciation of early-medieval contributions to the history of law and jurisprudence for entry-level students and scholars alike. Great Christian Jurists and Legal Collections in the First Millennium provides a fresh look, from a new perspective, enabling readers to see these familiar authors in a fresh light.